Vem är det som kör egentligen? : maskinanvändande och könsroller inom lantbruket : en intervjustudie med kvinnliga lantbrukare - Andermo, Stella (SLU/Dept. of Urban and Rural Development, 2010)

(untitled)
In this report female farmers use of technical equipment is investigated. There is little research made on this subject in Sweden, therefore this report can be seen as an explorative study. Research makes it clear that machinery, throughout history and even today, has been seen as a male area. Heavy machines are often associated with the same attributes as masculinity. Force, power, efficiency and control are some examples. In farming the division of labour has been rather strictly separated between the sexes. Doing work in the fields, where the horse has been substituted by the tractor as being the most important source of force, has been male work, while domestic work, milking, animal raising and other forms of farmyard work have been female tasks. With respect to the changes that have influenced agriculture, as well as the whole society in general during the last decades, it is reasonable to believe that women’s role in agriculture also has changed.